A Compartive Study of Changes in Trend in Housekeeping Department before and after Covid 19 (Global Journal of Management and Business Research, 2022)
Hotel industry housekeeping need to change after covid 19 because this is one of the most important concern in this scenario. The hotel industry not changes the trend, it also changes the eco-friendly product, subcontracting and training of the housekeeping employees. In this research paper I am going discuss about the new trend introduced in hotel industry after covid 19.housekeeping plays a most important role generating revenue. The hotel Industry need to change in this scenario as per comfort of the guest. Now a day#x2019;s hotels have lots of competition because there is not only one hotel, lots of hotel in the market. After covid guest are more self-conscious about health and hygiene tic so that housekeeping industry need introduced latest trend after covid 19.
Keywords: housekeeping; latest trend; covid 19